ANALISA SISTEM INFORMASI SURAT PENGANTAR MASYARAKAT ( SPM ) DI KELURAHAN TOMANG BERBASIS WEB - Besus Maula Sulthon (CKI ON SPOT, 2018)
ABSTRACT Letter of introduction of the community or in short (SPM) is a letter of introduction made by representatives of government agencies in rural areas i.e. wards, where the usefulness of SPM is very needed by all layers to leglisasai management the filing of a legal body, and the need for ease in making, maintaining SPM, as well as the status of SPM already made on the local neighborhood, the application of SPM SISFO present to mejawab it all with applications that are accessible can WEBASE anytime and anywhere by all who ask in any medium, such as mobile phone and computer. Keywords: SPM, System applications, Handphone, SISFO, Webase